The Urgency of Church Political Participation in Indonesia - Martin Luther Manao (Jurnal Pengabdian Pancasila (JPP), 2024)
Politics and the church are two things that are always debated in Christian circles because for some people the church does not need to involve itself in politics because it has a different call to service, but for others it encourages the church to contribute to political progress because the church is actually the light. and the salt of the earth and is indispensable for salting and illuminating the world of politics. The church cannot turn a blind eye to the social problems faced directly by the church because this is part of the ministry's duties that the church must pay attention to. Based on these debates, the author conducted research on the Urgency of Church Participation in Politics in Indonesia using a qualitative approach, namely research with descriptive analysis. In this research, the data used was obtained through a literature review sourced from research results, books, news, publication reports which were then analyzed descriptively. From the research results, it is concluded that Jesus is an example of the church's moral politics in fighting for freedom, truth and justice, so the practical politics that can be played by the church is moral politics through the church's participation in politics through an active role in controlling the government, criticizing government policies and fighting for truth and justice for all Indonesian citizens. The practical politics of the church in the midst of political problems in Indonesia are: First, with political education for church members so that they become intelligent voters who are able to vote well so that political leaders and representatives are found who are able to fight for the aspirations of the church.